In Silico Study of Bioactive Compounds from Yellow Bioherbal as Potential LpxC Protein Inhibitors for Controlling Pathogenic Bacteria in Broiler Chicken Intestinal - Zaen Yusuf; Muhammad Halim Natsir; Osfar Sjofjan (Jurnal Ilmu-Ilmu Peternakan)
Bioherbal, a feed additive made from rhizome extract, exhibited promising capabilities in eradicating pathogenic bacteria residing within the digestive tracts of broiler chickens. The LpxC protein, a biosynthetic regulator of lipid A (a critical component of gram-negative bacterial cell walls), was the focus of this research. Our primary objective was to assess the bioactive potential of bioherbal as a prospective inhibitor of UDP-3-O-(R-3-hydroxymyristoyl)-N-acetylglucosamine (LpxC) by employing in silico methods. Computational analyses were employed to scrutinize the interactions between the LpxC protein and various ligands on Bioherbal. Molecular docking served as the initial screening process, evaluating 48 bioactive compounds based on energy affinity, conformation values, and interactions with protein residues. The three compounds exhibiting the lowest binding affinities were subjected to molecular dynamics simulations. Molecular docking analysis revealed that most of the screened compounds exhibited low binding affinity for LpxC. Elephantorrhizol, zedoraldehyde, glechomanolide, demethoxycurcumin, curcumin, hexahydrocurcumin, gweicurculactone, germacrone, and 1,2-dihydrocurcumin exhibited lower binding affinities (<-7 kcal/mol). Elephantorrhizol, curcumin, and hexahydrocurcumin were selected for further analysis via molecular dynamics due to their similarity to native ligands. Molecular dynamics simulations revealed stable interactions of LpxC. In summary, these findings suggested that Bioherbal possesses the potential to function as an LpxC inhibitor, thereby offering a promising avenue for preventing the proliferation of gram-negative bacteria within the digestive tracts of broiler chickens. This computational study paves the way for further experimental investigations in this domain.